GENESIS OF VENTURE CAPITAL AND ITS EVOLUTION - Maria Yu. Ilyina (Статистика и экономика, 2016)
The current stage of many countries’ socio-economic development is characterized by a significant escalation of problems of their sustainable development. Stability of national economics, state’s position at the system of international relations, degree of its economic security become the key issue and depend not only on resource capabilities but of the innovative nature of capital and entrepreneurship.The article presents the genesis of venture capital, discloses a changes of its form. Based on it, the author offers his scheme of venture capital evolution.